Some results on MP-injectivity and MGP-injectivity of rings and modules - Zhanmin, Zhu (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We study MP-injective rings and MGP-injective rings satisfying some additional conditions. Using the concepts of MP-injectivity and MGP-injectivity of rings and modules, we present some new characterizations of QF-rings, semisimple Artinian rings, strongly regular rings, and simple Artinian rings.